Exploring Strengths-Based Approaches for Autistic Students in High School - White, Jia (Curtin University, 2025)
This thesis examines strengths-based approaches for autistic students in high schools, addressing research gaps. Through a scoping review and phenomenological studies of autistic adolescents, parents, and educators, it identifies the benefits and key elements of leveraging students’ strengths in order to enhance inclusion and educational experiences. Findings emphasise the need for tailored support, teacher professional development, and whole-school approaches, advocating for inclusive practices that celebrate neurodivergence and improve educational experiences and outcomes for autistic students.